Diagnosis and treatment of a closed and inverted metacarpal head fracture - Jinghong Wesley Yuan; Michael R. Boniello; David A. Fuller (Journal of the American College of Emergency Physicians Open)
Abstract This case report documents a rare inversion of a closed metacarpal head fracture in the setting of polytrauma. Although rare, hemispherical articular bones can fracture and rotate 180°. Because of the symmetry of the bone and the rarity of an inverted, metacarpal head fracture, a delay in diagnosis and subsequent treatment can occur, which can lead to a poor outcome. This is particularly true in the setting of polytrauma. A 38‐year‐old male, polytrauma patient presented to the emergency department (ED) after falling off a bridge and being struck by an oncoming vehicle. He presented with multiple surgical fractures of the upper and lower extremities as well as his pelvis. Three days after he was brought to the ED, x‐rays were performed of his painful left hand, which revealed an extra‐articular third metacarpal head fracture, for which he underwent open reduction of the closed fracture. Both collateral ligaments were intact and the head fragment had inverted within the constraints of these ligaments. Some of the ligament and capsular tissue remained attached to the head fragment along the radial and ulnar margins but was otherwise entirely covered with cartilage. The reduction maneuver was difficult but after the reduction was achieved, the fracture appeared stable and no internal fixation was used. Post reduction, the injury was splinted for 2 weeks and then early motion was allowed. The fracture has since healed, and the patient has attained near‐full function of the finger and joint.